2009
DOI: 10.1021/tx9001435
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Proposal for the Formation of Specific Immunogenic Complexes via a Radical Pathway: A Key Step in Allergic Contact Dermatitis to Olefinic Hydroperoxides

Abstract: The widespread use of scented products causes an increase of allergic contact dermatitis to fragrance compounds in Western countries today. Many fragrance compounds are prone to autoxidation, forming hydroperoxides as their primary oxidation products. Hydroperoxides are known to be strong allergens and to form specific immunogenic complexes. However, the mechanisms for the formation of the immunogenic complexes are largely unknown. We have investigated this mechanism for (5R)-5-isopropenyl-2-methyl-2-cyclohexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Previously, the reactivity of 3 with N-Ac-Cys-OMe in the presence of 5,10,15,20-tetraphenyl-21H,23H-porphyrin iron (III) chloride was studied by LC-MS. Adducts different from the ones we report here were described. 23 The authors observed also LC-MS peaks with m/z 328 and 344. They showed that 3 evolves easily to the formation of carvone in the presence of iron, 14 and proved thus accurately the formation of adducts by addition of the thiol group of cysteine either to the endocyclic bond of carvone or to the double bond of its isoprenyl group through a 2-electron reaction pathway, adducts having m/z 328.…”
Section: Reactivity With N-ac-cys-omementioning
confidence: 98%
“…Previously, the reactivity of 3 with N-Ac-Cys-OMe in the presence of 5,10,15,20-tetraphenyl-21H,23H-porphyrin iron (III) chloride was studied by LC-MS. Adducts different from the ones we report here were described. 23 The authors observed also LC-MS peaks with m/z 328 and 344. They showed that 3 evolves easily to the formation of carvone in the presence of iron, 14 and proved thus accurately the formation of adducts by addition of the thiol group of cysteine either to the endocyclic bond of carvone or to the double bond of its isoprenyl group through a 2-electron reaction pathway, adducts having m/z 328.…”
Section: Reactivity With N-ac-cys-omementioning
confidence: 98%
“…Chlorotrimethylsilane (2.00 g, 18.4 mmol, 2.34 mL) was added dropwise and stirring was continued for 45 min at 0 °C, followed by 1 h at room temperature. All volatiles were removed in vacuo and the residue was purified by flash chromatography, R f =0.48 (EtOAc), to give the desired methyl ester 14 (1.22 g, 6.9 mmol, 56 %) as colorless solid; all recorded spectra were identical to those reported in the literature …”
Section: Methodsmentioning
confidence: 55%
“…All volatiles were removed in vacuo and the residue was purified by flash chromatography, R f = 0.48 (EtOAc), to give the desired methyl ester 14 (1.22 g, 6.9 mmol, 56 %) as colorless solid;a ll recorded spectra were identical to those reported in the literature. [42] Methyl N-acetyl-S-(2-diethoxyphosphoryl-1-hydroxyiminoethyl)cysteinate (15): [22] Chloro-oxime 12 (525 mg, 2.3 mmol) was dissolved in dry CH 2 Cl 2 (10 mL) at 0 8Cb efore addition of (R)-methyl N-acetyl cysteinate [(R)-14,4 05 mg, 2.3 mmol] in CH 2 Cl 2 (5 mL). Et 3 N( 233 mg, 2.3 mmol, 0.32 mL) was added dropwise and stirring was continued for 90 min at 0 8C, followed by 2hat room temperature.…”
Section: Structure Verification Of Phosphonocystoximatementioning
confidence: 99%
“…Compounds 40 and 42 were prepared from intermediates 17 and 22 , respectively, which were acetylated using Ac 2 O; 34 tosyl group removal was effected using cesium carbonate. 32 Compounds 43 and 44 were synthesized by acetylating intermediates 29 and 8 , respectively (Scheme 5 of the Supplementary data).…”
Section: Resultsmentioning
confidence: 99%